Enhanced antibacterial and anticancer activities of plant extract mediated green synthesized zinc oxide-silver nanoparticles - Siti Nur Amalina, Mohamad Sukri; Shameli, Kamyar; Teow, Sin Yeang *; Chew, Jactty *; Ooi, Li Ting; Soon, Michiele Lee Kiun *; Nur Afini, Ismail; Moeini, Hassan (Frontiers Media, 2023)
This study presents a green synthesis approach for the fabrication of zinc oxide-silver nanoparticles (ZnO-Ag-NPs) using Punica granatum fruit peels extract as a natural reducing and stabilizing agent. This eco-friendly method offers a sustainable alternative to conventional methods that often employ toxic or hazardous chemicals. Antibacterial and anti-cancer activities of the green synthesized nanoparticles were then assessed in vitro. X-ray diffraction confirmed the production of ZnO-Ag-NPs with increasing crystallinity in higher pH values. The ZnO-Ag-NPs were found to be agglomerated with spherical Ag-NPs. Fourier Transform Infrared (FTIR) spectra revealed a broad band in ZnO-Ag-NPs ranging from 400-1 to 530 cm-1 with reduced intensity as compared to ZnO-NPs, indicating the formation of Ag-NPs on the surface of ZnO-NPs. The synthesized ZnO-Ag-NPs exhibited potent antibacterial activity against a broad spectrum of bacterial strains, particularly Gram-positive bacteria, with superior inhibition activity compared to ZnO-NPs. Moreover, ZnO-Ag-NPs showed a dose-dependent anti-proliferative effect on colorectal-, lung-, and cervical cancer cells. ZnO-Ag-NPs showed significantly greater efficacy in inhibiting cancer cell growth at a lower concentration of 31.25 μg/mL, compared to ZnO-NPs which required over 500 μg/mL, possibly due to the presence of silver nanoparticles (Ag-NPs). The results obtained from this study demonstrate the potential of green synthesis approaches in the fabrication of therapeutic nanomaterials for cancer treatment, as well as other biomedical applications.